Educating university & college peers on HIV/AIDS prevention - Ibrahim, Normala; Gyanchand Rampal, Lekhraj Rampal; Mohd Sidik, Sherina (Universiti Putra Malaysia Press, 2013)
Young people have been described as the centre of global HIV/AIDS pandemic and considered as population at risk of contracting HIV/AIDS. Their risk is predominantly associated with the two main modes of HIC transmission, namely, unprotected sexual intercourse and via injecting drug use (IDU). Their susceptibility to HIV infection is also contributed by their ignorant attitude, sense of invulnerability and lack of adequate information on HIV/AIDS This book is developed for assisting the youth to deliver knowledge, instill skills to their peers in order to prevent them from HIV infection. The book fives more emphasis on skills required by youth such as wise decision making and assertive behavior skills in order to deal more adaptively and effectively in situations where they are exposed to risky behaviours that lead to HIV/AIDS transmission. The development of this book is timely. It should offer young people strategies to combat their susceptibility to HIV infection.